2002
DOI: 10.1016/s0925-8388(02)00372-9
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence investigation of the Sm(III)-β-diketonates with sulfoxides, phosphine oxides and amides ligands

Abstract: In this paper we report on a photoluminescent investigation of complexes involving Sm-b-diketonates with sulfoxides, phosphine oxides and amides ligands. In the synthesis of the coordination compounds we used samarium tris(thenoyltrifluoroacetonate) dihydrated precursor with the following ligands (L): DBSO and PTSO sulfoxides; TPPO phosphine oxide and (PHA) N-phenylacetamide. They have 31 31 shown high orange luminescence characteristic of the Sm ion. The emission spectra of the Sm-complexes present narrow ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(51 citation statements)
references
References 14 publications
6
38
0
7
Order By: Relevance
“…parameters with those for other RE 3+ -complexes it is observed that the chemical environment around the rare earth ions in the tungstate systems is less polarizable than in the [RE(TTA) 3 (PTSO) 2 ] complex. 24 In the present investigation, the excitation spectra of the Gd 2 (WO 4 ) 3 :Tb 3+ system prepared by the Pechini and ceramic methods were also obtained at 77 K in the spectral range from 250 to 520 nm, under emission at 544 nm ( Figure 3). The spectrum of the Tb 5d transitions from the terbium ion, respectively.…”
Section: Photoluminescence Investigationmentioning
confidence: 78%
“…parameters with those for other RE 3+ -complexes it is observed that the chemical environment around the rare earth ions in the tungstate systems is less polarizable than in the [RE(TTA) 3 (PTSO) 2 ] complex. 24 In the present investigation, the excitation spectra of the Gd 2 (WO 4 ) 3 :Tb 3+ system prepared by the Pechini and ceramic methods were also obtained at 77 K in the spectral range from 250 to 520 nm, under emission at 544 nm ( Figure 3). The spectrum of the Tb 5d transitions from the terbium ion, respectively.…”
Section: Photoluminescence Investigationmentioning
confidence: 78%
“…Los complejos sólidos [RE(TTA)3(TPPO)2] (donde RE=Sm o Eu) fueron preparados por el método descrito en la Referencia [5], disolviendo los precursores hidratados [RE(TTA)3(H2O)2] y TPPO en solución etanólica en la razón molar 1:2 (complejo hidratado/TPPO). La solución fue entonces mezclada hasta que la precipitación del compuesto amarillo pálido estuviera completa.…”
Section: Methodsunclassified
“…No es posible detectar el H por la propia limitación de la técnica RBS para analizar elementos leves [4]. Sin embargo, la presencia de Sm, Eu, P, S y C, se muestra de acuerdo, en principio, con la fórmula empírica C60H42(RE)F9O8P2S3 [8], del complejo [RE(TTA)3(TPPO)2] (donde RE=Sm o Eu), por lo menos en lo que concierne a los elementos encontrados.…”
Section: +unclassified
“…The orange light was attained using the Sm 3+ ion [6], white con Dy 3+ [7], blue with Tm 3+ [8] and infrared emission was achieved with Er 3+ [9] and Yb 3+ [10], raising the interest on OLEDs devices for telecommunication applications. In contrast, the Gd 3+ ion has an energy gap between the 8 S7/2 ground state and first excited state 6 P7/2 at around 32000 cm -1 , and its complexes are used to study the energy of the triplet states T of the organic ligand [11].…”
Section: Introductionmentioning
confidence: 99%